Loss of Cdc42 causes abnormal optic cup morphogenesis and microphthalmia in mouse - Hofstetter, Katrina S.; Haas, Paula M.; Kuntz, Jonathon P.; Zheng, Yi; Fuhrmann, Sabine (Frontiers in Cellular Neuroscience, 2024)
Congenital ocular malformations originate from defective morphogenesis during early eye development and cause 25% of childhood blindness. Formation of the eye is a multi-step, dynamic process; it involves evagination of the optic vesicle, followed by distal and ventral invagination, leading to the formation of a two-layered optic cup with a transient optic fissure. These tissue folding events require extensive changes in cell shape and tissue growth mediated by cytoskeleton mechanics and intercellular adhesion. We hypothesized that the Rho GTPase Cdc42 may be an essential, convergent effector downstream of key regulatory factors required for ocular morphogenesis. CDC42 controls actin remodeling, apicobasal polarity, and junction assembly. Here we identify a novel essential function for Cdc42 during eye morphogenesis in mouse; in Cdc42 mutant eyes expansion of the ventral optic cup is arrested, resulting in microphthalmia and a wide coloboma. Our analyses show that Cdc42 is required for expression of the polarity effector proteins PRKCZ and PARD6, intercellular junction protein tight junction protein 1, b-catenin, actin cytoskeleton F-actin, and contractile protein phospho myosin light chain 2. Expression of RPE fate determinants OTX2 and MITF, and formation of the RPE layer are severely affected in the temporal domain of the proximal optic cup. EdU incorporation is significantly downregulated. In addition, mitotic retinal progenitor cells mis-localized deeper, basal regions, likely contributing to decreased proliferation. We propose that morphogenesis of the ventral optic cup requires Cdc42 function for coordinated optic cup expansion and establishment of subretinal space, tissue tension, and differentiation of the ventral RPE layer.